Sport-related hyperhomocysteinaemia: a putative marker of muscular demand to be noted for cardiovascular risk - Borrione, P.; Rizzo, M; Spaccamiglio, A.; Salvo, R. A.; Dovio, A.; Termine, A.; Parisi, A.; Fagnani, F.; Angeli, A.; Pigozzi, F. (British Journal of Sports Medicine, 2008)
Objective: Regular physical activity is associated with a reduction of cardiovascular morbidity and mortality; however, evidence of unfortunate cardiovascular events accompanying elite sport involvement continues to accumulate. To date, no information is available on possible peculiarities of the cardiovascular risk profile in athletes.